Pencegahan Infeksi Menular Seksual pada usia reproduktif melalui penyuluhan masyarakat di Kelurahan Bangunjiwo - Nur Azizah Indriastuti; Riski Oktafia; Luluk Rosida; Kirana Puji Ramadhanti Khaliri (Masyarakat Berdaya dan Inovasi, 2022)
Sexually transmitted infections (STIs) are one of the most widespread and dangerous infectious diseases. Human Immunodeficiency Virus (HIV) and Acquired Immunodeficiency Syndrome (AIDS) are global health problems that cause a fairly high mortality rate in the world (Ministry of Health, 2017). Based on data from the Progress Report on HIV AIDS & Sexually Transmitted Diseases (PIMS) Quarter IV of 2020, the Special Region of Yogyakarta ranks 13th as the province with the most HIV sufferers with a total of 6,921 cases and 1,608 AIDS cases. The case of HIV-AIDS in Yogyakarta attacks anyone and does not recognize age, social status, or gender which is not easy to predict. This is largely due to the low level of knowledge and understanding of the community regarding the transmission and impact of HIV/AIDS. Bangunjiwo Village is one of the villages located in Kasihan District, Bantul Regency, Yogyakarta. Judging from the data where the number of families in Bangunjiwo Village, which amounted to 8,284 families, there were 4,816 PUS (fertile age couples) who were vulnerable to contracting HIV. The education level of the people of Bangunjiwo village is still very low, as evidenced by the reproductive age of 18-56 years who did not finish elementary school reaching 3,396 and the number of people who only graduated from elementary school was very large, namely 5,442 people so that the reproductive age in Bangunjiwo village needs to be given education and training on how to prevent sexually transmitted infection